Different soil fertility conditions depending on different land use methods - Hoffmann, Sándor (Acta Agraria Debreceniensis, 2012)
In precision nutrient management the most important aspect is adaptation but we should consider the possibility of the long-term improvement of soil fertility within the less fertile landscape zones. This possibility can be evaluated principally by long-term field experiments, which are running on similar soil types. The results of these field experiments can indicate that which soil fertility status should be attained. Some more important soil fertility data, (such as pH, P-, K- and soil organic matter (SOM) content) of a long-term field experiment with increasing farmyard manure(FYM) doses or equivalent NPK fertilizers, set up on an Eutric cambisol, are presented. The yieldincreasing capacity of FYM doses was only 82%, as compared to the equivalent amount of mineral NPK, but long-term FYM treatments resulted in 10% higher SOM content than that of equivalent NPK fertilizer doses. The studies indicate that SOM content is a function of local climate and clay content of the soil, and neither long-term high FYM doses can increase SOM content steadily above a supposed steady-state value. However we have to make efforts to keep the optimum level. The lowest soil reactions developed both with the highest NPK doses and without any fertilization. AL-P2O5 content of soil was increased more by mineral fertilization than by FYM treatments, but in case of AL-K2O content there was no difference between the fertilization variants. However the highest doses of both fertilization variants increased soil nutrient content to an excessive degree. Wecould get very valuable data from the unfertilized control plots as well, where long-term yield data suppose 48 kg ha-1 year-1 air-borne N-input.